Grafted ferroelectric polymer film with high piezoelectric coefficient and preparation method thereof
By grafting small molecule side chains into polyvinylidene fluoride ferroelectric polymers, long-range ferroelectric interactions are broken, improving the piezoelectric coefficient of the material. This solves the problem of low piezoelectric coefficient in traditional polyvinylidene fluoride ferroelectric polymers, achieving efficient energy conversion and high-sensitivity sensing.
Patent Information
- Application Number
- CN202511718582.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-21
- Publication Date
- 2025-12-19
- Estimated Expiration
- 2045-11-21
AI Technical Summary
The traditional polyvinylidene fluoride ferroelectric polymer material has a low piezoelectric coefficient d33, which limits its energy conversion efficiency and sensing sensitivity, hindering its widespread application in flexible wearable electronics, medical and health fields.
By grafting small molecule side chains into polyvinylidene fluoride ferroelectric polymers, a branched polymer structure is formed through nucleophilic reactions, which breaks long-range ferroelectric interactions and promotes competition between the ferroelectric phase and the relaxor phase, thereby improving the piezoelectric coefficient of the material.
The piezoelectric coefficient d33 of the material is significantly improved to about -90 pC/N, which meets the requirements of high-sensitivity sensing and high-efficiency energy harvesting. Moreover, the preparation process is simple and suitable for large-scale production.
Smart Images

Figure CN121159905A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of flexible piezoelectric materials, and more particularly relates to a grafted ferroelectric polymer film with high piezoelectric coefficient and a preparation method thereof. BACKGROUND
[0002] With the rapid development of flexible wearable electronics, medical health, smart home and industrial detection, piezoelectric materials capable of realizing efficient mutual conversion between mechanical energy and electrical energy have become the core materials supporting the development of high-performance devices in these fields. Among them, polyvinylidene fluoride-based ferroelectric polymers have unique advantages that cannot be replaced by traditional inorganic piezoelectric materials in the fields of flexible wearable physiological signal sensors and medical minimally invasive device piezoelectric actuators, due to their excellent flexibility, lightweight, solution processing, stable ferroelectric performance and good biocompatibility with the human body. However, the piezoelectric coefficient of traditional polyvinylidene fluoride-based ferroelectric polymer materials is relatively low. d 33 As a core indicator for measuring the mechanical energy and electrical energy conversion capability of piezoelectric materials, d 33 a low piezoelectric coefficient directly limits the energy conversion efficiency, sensing sensitivity and other performance of the material, and seriously hinders the wider application of ferroelectric polymers.
[0003] Therefore, there is an urgent need for a new method that can efficiently improve the piezoelectric performance of polyvinylidene fluoride-based ferroelectric polymers to meet the urgent demand for high-performance piezoelectric materials in various fields. SUMMARY
[0004] In view of the above defects or improvement needs of the prior art, the present application provides a grafted ferroelectric polymer film with high piezoelectric coefficient and a preparation method thereof, which solves the problem of low piezoelectric coefficient of traditional polyvinylidene fluoride-based ferroelectric polymer materials, which hinders the wider application of ferroelectric polymers.
[0005] To achieve the above-mentioned purpose, according to one aspect of the present application, a preparation method of a grafted ferroelectric polymer film with high piezoelectric coefficient is provided, comprising: S1, selecting a polyvinylidene fluoride-based ferroelectric polymer to be dissolved in an organic solvent to obtain a polymer solution; S2, adding a grafting agent reagent to the polymer solution and mixing uniformly to obtain a mixed solution; S3, uniformly casting the mixed solution on the surface of a glass substrate, heating in an oven to volatilize the solvent, then increasing the oven temperature for grafting reaction to obtain a grafted film; S4, after the oven is naturally cooled to room temperature, the grafted film is peeled off from the glass substrate, and a polarization process is used to obtain a grafted ferroelectric polymer film with high piezoelectric coefficient.
[0006] The application provides a preparation method of a grafted ferroelectric polymer film with a high piezoelectric coefficient. polyvinylidene fluoride-trifluoroethylene, wherein the content of trifluoroethylene is 35 mol% to 45 mol%; or polyvinylidene fluoride-tetrafluoroethylene, wherein the content of tetrafluoroethylene is 5 mol% to 10 mol%; or polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene, wherein the content of trifluoroethylene is 30 mol% to 40 mol% and the content of chlorofluoroethylene is 5 mol% to 7 mol%; or polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene, wherein the content of trifluoroethylene is 30 mol% to 40 mol% and the content of chlorofluoroethylene is 5 mol% to 7 mol%.
[0007] The application provides a preparation method of a grafted ferroelectric polymer film with a high piezoelectric coefficient, wherein the organic solvent in S1 is selected from one of cyclohexanone, N, N-dimethylamide, dimethyl sulfoxide and N-methyl pyrrolidone.
[0008] The application provides a preparation method of a grafted ferroelectric polymer film with a high piezoelectric coefficient, wherein the concentration of the polyvinylidene fluoride-based ferroelectric polymer in the polymer solution prepared in S1 is 40 to 100 mg / ml.
[0009] The application provides a preparation method of a grafted ferroelectric polymer film with a high piezoelectric coefficient, wherein the grafting agent reagent in S2 is a monoamine small molecule grafting agent reagent.
[0010] The application provides a preparation method of a grafted ferroelectric polymer film with a high piezoelectric coefficient, wherein the grafting agent reagent is one or a combination of the following: n-propylamine, n-butylamine, n-hexylamine, n-decylamine, cyclopentylamine, cyclohexylamine and aniline.
[0011] The application provides a preparation method of a grafted ferroelectric polymer film with a high piezoelectric coefficient, wherein the molar ratio of the grafting agent to the polyvinylidene fluoride-based ferroelectric polymer in the mixed solution prepared in S2 is 0.6 to 4.5:100.
[0012] The application provides a preparation method of a grafted ferroelectric polymer film with a high piezoelectric coefficient, wherein the reaction conditions of the grafting reaction in S3 are as follows: the oven temperature is increased to 200 to 220°C under an air or inert gas atmosphere, and the reaction time is 2 to 4 h.
[0013] The application provides a preparation method of a grafted ferroelectric polymer film with a high piezoelectric coefficient, wherein the polarization process in S4 comprises a contact polarization process or a corona polarization process. The polarization parameters of the contact polarization process are a direct current electric field of 100-150 MV / m and a polarization time of 10-30 min; the polarization parameters of the corona polarization process are a voltage of 10-16 kV, a needle-film distance of 3-6 cm, and a polarization time of 10 min-60 min.
[0014] According to another aspect of the present application, a ferroelectric polymer thin film with a high piezoelectric coefficient is provided, which is prepared by the preparation method of the ferroelectric polymer thin film with a high piezoelectric coefficient.
[0015] Overall, compared with the prior art, the ferroelectric polymer thin film with a high piezoelectric coefficient and the preparation method thereof provided by the present application have the following advantages: 1. The grafting modification step is integrated into the film material preparation step, the polyvinylidene fluoride-based ferroelectric polymer is modified by using grafting side chains under heating conditions, small molecule side chains are grafted in the traditional polyvinylidene fluoride-based ferroelectric polymer through nucleophilic reaction, the relative stability of different molecular conformation energies in the ferroelectric polymer can be controlled, so that the ferroelectric phase and the relaxor phase in the ferroelectric polymer compete with each other, and the piezoelectric coefficient of the material is significantly improved; 2. The present application is based on a solution casting process, which is simple in procedure, short in production cycle, and has the potential for large-scale manufacturing; 3. The grafting modified ferroelectric polymer thin film prepared by the present application has uniform thickness, smooth surface, and significantly improved elongation at break compared with before modification, and is more suitable for the human body fitting requirements of wearable devices; 4. The piezoelectric phase of the polyvinylidene fluoride-based polymer is significantly enhanced, and the maximum d 33 about -90 pC / N, which meets the requirements of high-sensitivity sensing and high-efficiency energy collection. BRIEF DESCRIPTION OF DRAWINGS
[0016] Figure 1 is a flowchart of the preparation method of the ferroelectric polymer thin film with a high piezoelectric coefficient provided by the present application.
[0017] Figure 2 is a reaction mechanism diagram of the grafting reaction provided by the present application.
[0018] Figure 3 is an X-ray diffraction and infrared spectrum diagram of the samples obtained in Examples 1-4 and the original polymer (P(VDF-TrFE) 55 / 45 mol%).
[0019] Figure 4 is a comparison diagram of the elongation at break of the samples obtained in Examples 1-4 and the original polymer (P(VDF-TrFE) 55 / 45 mol%).
[0020] Figure 5 is a physical map of the sample obtained in Example 3 of the present application and a schematic diagram of thickness uniformity in different regions.
[0021] Figure 6 is a physical map of the sample obtained in Example 1-4 of the present application and the original polymer (P(VDF-TrFE) 55 / 45mol%) from d 33 The tester measured d 33 Comparison chart. DETAILED DESCRIPTION
[0022] In order to make the objects, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in combination with the drawings and examples. It should be understood that the specific examples described herein are only used to explain the present application and do not limit the present application. In addition, the technical features involved in each embodiment of the present application described below can be combined with each other as long as they do not conflict with each other.
[0023] Please refer to Figure 1 The present embodiment provides a preparation method of a grafted ferroelectric polymer film with high piezoelectric coefficient, which comprises the following steps: S1, selecting a polyvinylidene fluoride-based ferroelectric polymer to be dissolved in an organic solvent to obtain a polymer solution; S2, adding a grafting agent reagent to the polymer solution and mixing uniformly to obtain a mixed solution; S3, uniformly casting the mixed solution on the surface of a glass substrate, heating in an oven to volatilize the solvent, then increasing the oven temperature to perform grafting reaction to obtain a grafted film; S4, after the oven is naturally cooled to room temperature, the grafted film is peeled off from the glass substrate, and a polarization process is performed to obtain a grafted ferroelectric polymer film with high piezoelectric coefficient.
[0024] The traditional grafting modification strategy generally focuses on inducing polar conformation, which has very limited effect on the improvement of the piezoelectric coefficient when used in the field of ferroelectric polymers. The embodiment proposes to combine grafting modification with film material preparation process, that is, to integrate the grafting modification step into the film material preparation step. Specifically, a grafting agent is added to a polyvinylidene fluoride-based ferroelectric polymer solution, and after sufficient mixing, the mixed solution is cast on a glass substrate, heated and dried to evaporate the solvent, and then the grafting reaction between the polymer and the grafting agent is directly carried out by increasing the temperature. Through special grafting process design, the grafting agent is used to directly graft the polyvinylidene fluoride-based ferroelectric polymer at a set temperature. During the grafting reaction, small molecular side chains can be grafted on the polymer through nucleophilic reaction to form a branched polymer structure. The presence of short branches increases the distance between the chains and improves the conformational disorder, which helps to break the long-range ferroelectric interaction and form a stable relaxor phase. The competition between the two phases promotes the significant improvement of the piezoelectric coefficient of the material. d 33
[0025] Referring to Figure 2 , the reaction mechanism of the grafting reaction in the embodiment is as follows: the polyvinylidene fluoride-based ferroelectric polymer is first dehydrofluorinated to form a carbon-carbon double bond under the catalysis of alkali, then the amine grafting agent reacts with the carbon-carbon double bond to form a side chain connected to the polymer, and finally the dehydrofluorination is further carried out under heating to form a more stable carbon-nitrogen double bond. Thus, small molecular side chains are grafted on the polymer to improve the conformational disorder, which helps to break the long-range ferroelectric interaction and form a stable relaxor phase. The competition between the two phases promotes the significant improvement of the piezoelectric coefficient of the material.
[0026] In the embodiment S1, the polyvinylidene fluoride-based ferroelectric polymer is in powder form; in S2, the grafting agent is in liquid form. After adding the grafting agent to the polymer solution in a certain proportion, the mixed solution is obtained by stirring at a speed of 200-400 rpm / min for 1-2 h to mix uniformly; in S3, the mixed solution is uniformly cast on the surface of a smooth glass substrate, and the solvent is volatilized by heating in an oven at 60 °C for 8 h.
[0027] In some embodiments, the polyvinylidene fluoride-based ferroelectric polymer in S1 is: polyvinylidene fluoride-trifluoroethylene, wherein the content of trifluoroethylene is 35 mol% to 45 mol%; or polyvinylidene fluoride-tetrafluoroethylene, wherein the content of tetrafluoroethylene is 5 mol% to 10 mol%; or polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene, wherein the content of trifluoroethylene is 30 mol% to 40 mol%, and the content of chlorofluoroethylene is 5 mol% to 7 mol%; Or, polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene, the content of trifluoroethylene is 30 mol%~40 mol%, the content of chlorotrifluoroethylene is 5 mol%~7 mol%.
[0028] In some embodiments, the organic solvent in S1 is selected from one of cyclohexanone, N,N-dimethylformamide, dimethyl sulfoxide, N-methyl pyrrolidone.
[0029] Optionally, the concentration of the polyvinylidene fluoride-based ferroelectric polymer in the polymer solution prepared in S1 is 40~100 mg / ml.
[0030] Further, the grafting agent reagent in S2 is a small-molecule monoamine grafting agent reagent. The grafting agent reagent can be a pure grafting agent or a grafting agent solution, which can meet the requirement of the ratio of the grafting agent to the polymer in the reagent, and is not specifically limited. The present embodiment proposes to use a small-molecule monoamine grafting agent to graft and modify the polymer, so that the side chain of the small molecule can be grafted on the polymer, thereby better realizing the improvement of the piezoelectric coefficient of the film material.
[0031] In some embodiments, the grafting agent reagent is one or a combination of more than one of n-propylamine, n-butylamine, n-hexylamine, n-decylamine, cyclopentylamine, cyclohexylamine, and aniline.
[0032] Optionally, the molar ratio of the grafting agent to the polyvinylidene fluoride-based ferroelectric polymer in the mixed solution prepared in S2 is 0.6~4.5:100.
[0033] In some embodiments, the reaction conditions of the grafting reaction in S3 are as follows: the oven temperature is increased to 200~220°C under an air or inert gas atmosphere, and the reaction time is 2~4 h.
[0034] In some embodiments, the polarization process in S4 includes a contact polarization process or a corona polarization process. The polarization parameters of the contact polarization process are a direct current electric field of 100~150 MV / m and a polarization time of 10~30 min, and the polarization parameters of the corona polarization process are a voltage of 10~16 kV, a needle-film distance of 3~6 cm, and a polarization time of 10 min~60 min.
[0035] In other embodiments, a grafting ferroelectric polymer film with a high piezoelectric coefficient is also provided, which is prepared by the preparation method of the grafting ferroelectric polymer film with a high piezoelectric coefficient according to any one of the above embodiments.
[0036] The preparation process and effects of the grafting ferroelectric polymer film with a high piezoelectric coefficient are described below through specific embodiments.
[0037] Example 1: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to configure a polymer solution with a concentration of 60 mg / ml, stirred at a rate of 400 rpm / min for 12 h at 40 °C, n-butylamine was added to the uniformly stirred polymer solution at a molar ratio of 100:0.6, stirred at a rate of 400 rpm / min for 1 h at 40 °C, then the polymer solution was cast on a glass substrate, the solvent was dried at 60 °C, then the temperature was continued to be raised to 220 °C for 3 h for grafting reaction, after the temperature slowly decreased to room temperature, it was peeled off from the substrate, contact polarization was carried out using a direct current electric field of 120 MV / m, and the polarization time was 15 min.
[0038] Example 2: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to configure a polymer solution with a concentration of 60 mg / ml, stirred at a rate of 400 rpm / min for 12 h at 40 °C, n-butylamine was added to the uniformly stirred polymer solution at a molar ratio of 100:1.2, stirred at a rate of 400 rpm / min for 1 h at 40 °C, then the polymer solution was cast on a glass substrate, the solvent was dried at 60 °C, then the temperature was continued to be raised to 220 °C for 3 h for grafting reaction, after the temperature slowly decreased to room temperature, it was peeled off from the substrate, contact polarization was carried out using a direct current electric field of 120 MV / m, and the polarization time was 15 min.
[0039] Example 3: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to configure a polymer solution with a concentration of 60 mg / ml, stirred at a rate of 400 rpm / min for 12 h at 40 °C, n-butylamine was added to the uniformly stirred polymer solution at a molar ratio of 100:2.25, stirred at a rate of 400 rpm / min for 1 h at 40 °C, then the polymer solution was cast on a glass substrate, the solvent was dried at 60 °C, then the temperature was continued to be raised to 220 °C for 3 h for grafting reaction, after the temperature slowly decreased to room temperature, it was peeled off from the substrate, contact polarization was carried out using a direct current electric field of 120 MV / m, and the polarization time was 15 min.
[0040] Example 4: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to configure a polymer solution with a concentration of 60 mg / ml, stirred at a rate of 400 rpm / min for 12 h at 40 °C, n-hexylamine was added to the uniformly stirred polymer solution at a molar ratio of 100:4.5, stirred at a rate of 400 rpm / min for 1 h at 40 °C, then the polymer solution was cast on a glass substrate, the solvent was dried at 60 °C, then the temperature was continuously increased to 220 °C for 3 h for grafting reaction, after the temperature slowly decreased to room temperature, it was peeled off from the substrate, contact polarization was carried out using a direct current electric field of 120 MV / m, and the polarization time was 15 min.
[0041] Example 5: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to configure a polymer solution with a concentration of 60 mg / ml, stirred at a rate of 400 rpm / min for 12 h at 40 °C, n-hexylamine was added to the uniformly stirred polymer solution at a molar ratio of 100:0.6, stirred at a rate of 400 rpm / min for 1 h at 40 °C, then the polymer solution was cast on a glass substrate, the solvent was dried at 60 °C, then the temperature was continuously increased to 220 °C for 3 h for grafting reaction, after the temperature slowly decreased to room temperature, it was peeled off from the substrate, contact polarization was carried out using a direct current electric field of 120 MV / m, and the polarization time was 15 min.
[0042] Example 6: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to configure a polymer solution with a concentration of 60 mg / ml, stirred at a rate of 400 rpm / min for 12 h at 40 °C, n-hexylamine was added to the uniformly stirred polymer solution at a molar ratio of 100:1.2, stirred at a rate of 400 rpm / min for 1 h at 40 °C, then the polymer solution was cast on a glass substrate, the solvent was dried at 60 °C, then the temperature was continuously increased to 220 °C for 3 h for grafting reaction, after the temperature slowly decreased to room temperature, it was peeled off from the substrate, contact polarization was carried out using a direct current electric field of 120 MV / m, and the polarization time was 15 min.
[0043] Example 7: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Then, n-hexylamine was added to the homogenized polymer solution at a molar ratio of 100:2.25. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0044] Example 8: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Then, n-hexylamine was added to the homogenized polymer solution at a molar ratio of 100:4.5. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0045] Example 9: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Then, n-decylamine was added to the homogenized polymer solution at a molar ratio of 100:2.25. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0046] Example 10: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Cyclopentanylamine was added to the homogenized polymer solution at a molar ratio of 100:2.25. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0047] Example 11: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Cyclohexylamine was added to the homogenized polymer solution at a molar ratio of 100:2.25. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0048] Example 12: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Then, n-propylamine was added to the homogenized polymer solution at a molar ratio of 100:2.25. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0049] Example 13: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of N,N-dimethylamide solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C and 400 rpm / min for 12 h. Then, n-butylamine was added to the homogenized polymer solution at a molar ratio of 100:0.6. The solution was stirred at 40 °C and 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0050] Example 14: 300 mg of P(VDF-TFE) 95 / 5 mol% was added to 5 ml of N,N-dimethylamide solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Then, n-butylamine was added to the homogenized polymer solution at a molar ratio of 100:0.6. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0051] Comparative Example 1: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Aniline was added to the homogenized polymer solution at a molar ratio of 100:2.25. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0052] Comparative Example 2: 300 mg of P(VDF-TrFE) 55 / 45 mol% was added to 5 ml of cyclohexanone solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Then, n-decylamine was added to the homogenized polymer solution at a molar ratio of 100:4.5. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate, and the solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate and contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0053] Comparative Example 3: 300 mg of P(VDF-TrFE) 80 / 20 mol% was added to 5 ml of cyclohexanone solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Then, n-butylamine was added to the homogenized polymer solution at a molar ratio of 100:2.25. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0054] Comparative Example 4: 300 mg of P(VDF-TrFE) 80 / 20 mol% was added to 5 ml of cyclohexanone solvent to prepare a polymer solution with a concentration of 60 mg / ml. The solution was stirred at 40 °C at a rate of 400 rpm / min for 12 h. Then, n-butylamine was added to the homogenized polymer solution at a molar ratio of 100:4.5. The solution was stirred at 40 °C at a rate of 400 rpm / min for 1 h. The polymer solution was then cast onto a glass substrate. The solvent was dried at 60 °C. The temperature was then raised to 220 °C and held for 3 h to carry out the grafting reaction. After the temperature slowly dropped to room temperature, the grafting was peeled off from the substrate. Contact polarization was performed using a DC electric field of 120 MV / m for 15 min.
[0055] The piezoelectric coefficients of the films prepared in the above specific embodiments and comparative examples are detailed in Table 1 below: Table 1. Examples and Comparative Examples and Original Polymers d 33 The tester measured d 33 contrast
[0056] As can be seen from Examples 1-13 and Comparative Examples 1-2 above, when the polymer uses P(VDF-TrFE) 55 / 45 mol%, the type of grafting agent, the range of molar ratio of grafting agent to polymer, and the type of organic solvent in the polymer solution provided by the present invention all improve the piezoelectric coefficient of the film material prepared by the original P(VDF-TrFE) 55 / 45 mol%. The improvement in piezoelectric coefficient is particularly significant when the molar ratio of grafting agent to polymer is in the range of 1.2-2.25:100. The preferred grafting agent is any one of n-propylamine, n-butylamine, n-hexylamine, n-decylamine, cyclopentylamine, and cyclohexylamine. The comparison between Example 14 and the original P(VDF-TFE) 95 / 5 mol%, and the comparison between Comparative Examples 3-4 and the original P(VDF-TrFE) 80 / 20 mol%, demonstrates that the grafting modification process provided by this invention can also improve the piezoelectric coefficient of the prepared membrane material when the polymer concentration ratio provided by this invention is not the preferred polymer concentration ratio provided by this invention. This demonstrates the effectiveness of the grafting modification process provided by this invention.
[0057] Appendix Figure 3 X-ray diffraction and infrared spectra of the samples obtained in Examples 1-4 and the original b polymer (P(VDF-TrFE) 55 / 45 mol%); wherein Figure 3 In the figure, a represents X-ray diffraction and b represents the infrared spectrum at the corresponding wavenumber of the all-trans conformation. As the grafting concentration increases, the content of the all-trans conformation in the material gradually decreases, while the content of the relaxor phase gradually increases. Appendix Figure 4 The graph shows a comparison of the fracture growth rate of the samples obtained in Examples 1-4 and the original polymer (P(VDF-TrFE) 55 / 45 mol%). As the grafting concentration increases, the elongation at break of the material also increases significantly. Appendix Figure 5 The images shown are physical pictures of the sample obtained in Example 3 and schematic diagrams illustrating the thickness uniformity in different regions. Figure 5 In the diagram, 'a' is a physical image and 'b' is a schematic diagram of the thickness uniformity in different regions. The film thickness variation in different regions is within 10%, indicating good uniformity. Appendix Figure 6 The samples obtained in Examples 1-4 of this invention and the original polymer (P(VDF-TrFE) 55 / 45 mol%) were derived from... d 33 The tester measured d 33 Comparison chart.
[0058] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a thin film grafted with a high voltage coefficient of ferroelectric polymer, characterized in that, include: S1, a polymer solution is obtained by dissolving polyvinylidene fluoride ferroelectric polymer in an organic solvent; S2, add grafting agent to the polymer solution and mix evenly to obtain a mixed solution; S3, the mixed solution is uniformly cast onto the surface of a glass substrate, heated in an oven to evaporate the solvent, and then the oven temperature is increased to carry out a grafting reaction to obtain a grafted film. S4. After the oven has cooled naturally to room temperature, the grafted film is peeled off from the glass substrate and processed using a polarization process to obtain a high voltage coefficient grafted ferroelectric polymer film.
2. The method for preparing a high-voltage grafted ferroelectric polymer thin film as described in claim 1, characterized in that, The polyvinylidene fluoride ferroelectric polymer mentioned in S1 is: Polyvinylidene fluoride-trifluoroethylene, wherein the trifluoroethylene content is 35 mol%~45 mol%; Alternatively, it may be polyvinylidene fluoride-tetrafluoroethylene, wherein the tetrafluoroethylene content is 5 mol%~10 mol%; Alternatively, it may be polyvinylidene fluoride-trifluoroethylene-chlorofluoroethylene, wherein the content of trifluoroethylene is 30 mol%~40 mol% and the content of chlorofluoroethylene is 5 mol%~7 mol%. Alternatively, it can be polyvinylidene fluoride-trifluoroethylene-trifluorochloroethylene, with a trifluoroethylene content of 30 mol%~40 mol% and a trifluorochloroethylene content of 5 mol%~7 mol%.
3. The method for preparing a high-voltage grafted ferroelectric polymer thin film as described in claim 1, characterized in that, The organic solvent mentioned in S1 is selected from one of cyclohexanone, N,N-dimethylamide, dimethyl sulfoxide, and N-methylpyrrolidone.
4. The method for preparing a high-voltage grafted ferroelectric polymer thin film as described in claim 1, characterized in that, The concentration of polyvinylidene fluoride ferroelectric polymer in the polymer solution prepared in S1 is 40~100 mg / ml.
5. The method for preparing a high-voltage grafted ferroelectric polymer thin film as described in any one of claims 1-4, characterized in that, The grafting agent mentioned in S2 is a monoamine small molecule grafting agent.
6. The method for preparing a high-voltage grafted ferroelectric polymer thin film as described in claim 5, characterized in that, The grafting agent is one or more combinations of n-propylamine, n-butylamine, n-hexylamine, n-decylamine, cyclopentylamine, cyclohexylamine, and aniline.
7. The method for preparing a high-voltage grafted ferroelectric polymer thin film according to any one of claims 1-4, characterized in that, The molar ratio of grafting agent to polyvinylidene fluoride ferroelectric polymer in the mixed solution prepared in S2 is 0.6~4.5:
100.
8. The method for preparing a thin film grafted with a high voltage coefficient of ferroelectric polymer as described in any one of claims 1-4, characterized in that, The grafting reaction conditions described in S3 are as follows: under an air or inert gas atmosphere, the oven temperature is raised to 200~220°C, and the reaction time is 2~4 h.
9. The method for preparing a thin film grafted with a high voltage coefficient of ferroelectric polymer as described in any one of claims 1-4, characterized in that, The polarization process in S4 includes contact polarization or corona polarization. The polarization parameters for the contact polarization process are a DC electric field of 100~150 MV / m and a polarization time of 10~30 min; the polarization parameters for the corona polarization process are a voltage of 10~16 kV, a needle tip-film distance of 3~6 cm, and a polarization time of 10 min~60 min.
10. A thin film of grafted ferroelectric polymer with a high voltage coefficient, characterized in that, The thin film with a high voltage coefficient grafted ferroelectric polymer is prepared by any one of the above claims 1-9.
Citation Information
Patent Citations
Preparation method of ferroelectric polymer film with high piezoelectric coefficient
CN118772457A
Preparation method of high-performance flexible piezoelectric film
CN119072213A
Diamine monomer cross-linked modified fluorine-containing ferroelectric polymer, preparation method and device
CN119570179A
Blended relaxor ferroelectric polymer super-ion solid electrolyte as well as preparation method and application thereof
CN120149521A
Polyvinylidene fluoride based ferroelectric polymer and preparation method thereof
CN120795221A